The Effect of Price Balance And Location On Consumer Purchase Interest In The Bode Lor Caplek Market - Diyanah Zulfa; Afiqoh Agustin; Achmad Otong Bushtomi (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2024)
Bode Lor Caplek Market is a long-established village market on Kisabalanang Street. Bode Lor Village is famous for the woven fabric trade, the traders utilize the shoulder of the road to be used as a place for them to make a living. Then, because it causes congestion, the Bode Lor Village government provides facilities in the form of kiosks so that traders can sell in an orderly manner. In 2023 the Bode Lor Caplek Market was developed into a semi-modern market, formerly known as the source of congestion in Bode Lor Village. The revitalization of the modern art market resulted in 320 stalls and stalls with 282 traders. Caplek Bode Lor Market has a Vision and Mission, namely